Doses de composto orgânico e consorciação com crotalaria spectabilis sobre nematoides e produtividade da figueira - Pereira, Jordana de Jesus Santos (2017)
The fig (Ficus carica L.) is a fruitful species with great worldwide expansion, since it is considered a species of temperate climate, but that presents / displays good adaptation to a great diversity of climates and solos. Among the phytosanitary problems occurring in ficiculture, nematodes are the most important. The objective of the present study is to evaluate the influence of the application of different doses of organic compost and the intercropping with Crotalaria spectabilis on nematode population density and fig yield. The experiment was conducted in the orchard already installed, from September of the year 2015 to September 2016. The plants were arranged in a spacing of 4 m between rows and 2 m between plants. The treatments were five doses of organic compound, having as reference the recommended amount of nitrogen for the fig tree crop, combined with the presence or absence of Crotalaria spectabilis in a consortium. Five phytoematoid species were identified in the orchard, being Meloidogyne incognita, Pratylenchus sp., Helicotylenchus sp., Criconemoide sp. and Rotylenchulus sp .. M. incognita was present in higher population densities and with dominance over 90% in the three evaluation periods. This species was not affected by the doses of organic compound nor by the use of C. spectabilis. The productivity of the fig trees increased with the increase of the dose of applied organic compound.